2014
DOI: 10.1111/ahe.12130
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Parturition Time in Queens using Radiography and Ultrasonography

Abstract: This study investigated the prediction of parturition in queens, as well as the effects of the queens' age and weight and the litter size on the accuracy of the prediction. A prospective study was performed in 24 purebred queens of 11 different breeds, all in normal body condition, using radiographic and ultrasonographic measurements of foetal femoral length (FL) and biparietal diameter (BPD) of fœtal skull that apply to different breeds. Pregnant queens with aborted or malformed foetuses were excluded. The ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 29 publications
1
20
0
1
Order By: Relevance
“…In Brito et al study like in our work, GS and fetal measurements increased as gestational aged advanced. The linear increase in biparietal diameter during pregnancy founded by Gatel et al [15] is in agreement with our results in which the same parameter increases with the days after mating.…”
supporting
confidence: 94%
See 4 more Smart Citations
“…In Brito et al study like in our work, GS and fetal measurements increased as gestational aged advanced. The linear increase in biparietal diameter during pregnancy founded by Gatel et al [15] is in agreement with our results in which the same parameter increases with the days after mating.…”
supporting
confidence: 94%
“…Hence, ultrasonographic measurements could be useful to estimate gestational age in almost every breed of queen and to confirm that measurements are within the expected range to a given day of gestation. Gatel et al [15] observed that the time to parturition increased more the queen weighed before mating, suggesting that the queens' size influenced gestational length. In addition, the time to parturition was shorter when the queen was older [15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations